Reaching the Unreached: Providing Quality Care to HIV-Infected Children through Telemedicine—An Innovative Pilot Initiative from Maharashtra, India - Mamta Manglani; Yashwant Gabhale; Mamatha Murad Lala; Sudha Balakrishnan; Khanindra Bhuyan; B. B. Rewari; Maninder Singh Setia (International Journal of Pediatrics)
Background. The National AIDS Control Organization (NACO) of India created the Regional Pediatric Antiretroviral Therapy (ART) Center; this was subsequently upgraded to seven Pediatric Centers of Excellence (PCoEs) to strengthen the quality of treatment and care of children living with HIV/AIDS (CLHAs). In October 2013, the pediatric HIV telemedicine initiative, an e-decentralized (care provided by local healthcare providers and support provided by a central agency through telemedicine facilities) model of expert pediatric HIV care and referral services, was established as a pilot project at the Pediatric Center of Excellence for HIV Care in Maharashtra. We designed the present study to compare management, compliance to ART, and mortality in children in the ART centers linked to the PCoE through telemedicine versus those that are not linked to the PCoE. Methods. It was a retrospective cross-sectional study of secondary data from CLHAs from October 2013 through August 2015 in the ART centers to document the intermediate outcomes and to determine if the initiative has improved the quality of care for the CLHAs enrolled in the linked ART centers with nonlinked ART centers. The centers in which the telemedicine sessions were conducted regularly were called linked-regular centers and in whom it was conducted irregularly (less than the median of 12 videoconference cases), it was called a linked-irregular center. Data from 2803 children in 31 linked (1365 in irregular and 1438 in regular centers) and 2608 children in 28 nonlinked centers were analyzed. The outcomes in children in the pre-ART group (ART naïve) were (1) alive on pre-ART, (2) lost to follow-up on pre-ART, (3) death during the pre-ART period, (4) eligible but not initiated on ART, and (5) missing baseline and latest CD4 counts. The outcomes of children on ART were (1) alive on ART, (2) lost to follow-up on ART, (3) death on ART, and (4) missing baseline and latest CD4 counts. Results. We found that a higher proportion of children in the linked-regular centers (79% vs. 70%, p<0.001) and linked-irregular centers (76% vs. 70%, p=0.04) was alive compared with that in the nonlinked centers in the pre-ART group. In this group, the proportion of children with missing baseline CD4 counts and latest CD4 counts was significantly low in linked (regular centers) centers. In the ART group, we found that a higher proportion of children in the linked-regular centers was alive compared with that in the linked-irregular centers (77% vs. 69%, p<0.001); the proportion was not significantly different in nonlinked centers (77% vs. 78%, p=0.56). In this group, the proportion of missing baseline CD4 counts was significantly lower in the linked-regular centers (3% vs 13%, p<0.001) and linked-irregular centers (1% vs. 13%, p<0.001) compared with that in the nonlinked centers. Furthermore, the latest CD4 counts were missing in a significantly lower proportion of children in the linked-regular centers compared with those in the linked-irregular centers (6% vs. 18%, p<0.001) and nonlinked centers (6% vs. 18%, p<0.001). Conclusion. Our study shows that the centers linked through telemedicine performed better in terms of patient care and treatment, with a lesser loss to follow-up and lesser deaths in CLHA. Overall, this pilot project of telemedicine for pediatric HIV has been proven to be acceptable, feasible, and effective in improving the quality of care for children living with HIV across the state of Maharashtra.